APTIDÃO DE HÍBRIDOS EXPERIMENTAIS DE MORANGUEIRO OBTIDOS A PARTIR DE CRUZAMENTOS INTRAESPECÍFICOS - Barth, Eneide (2017)
The development of cultivars of strawberry national (Fragaria x ananassa) adapted to the climatic conditions of Brazil and with defined aptitude can meet the specifics of different segments of the consumer market. The objective of this work was to select the hybrid of strawberry, with potential for consumption in natura, by applying three selection indexes, providing a better balance of attributes with a simultaneous evaluation of characteristics. Were evaluated hybrids obtained from the cross between seven commercial cultivars, being defined the selection of 10% of them. Were using non-parametric indices Mulamba and Mock (1978) and Genotype-ideotype, and parametric index of Smith (1936) and Hazel (1943). The experiment was conducted in design of increased blocks, using as witnesses the commercial cultivars Camarosa and Camino Real. For each index, were assigned two sets of economic weights distinguishing fitness for consumption in natura and industry. The productive characteristics were evaluated: number and average mass of commercial fruits, mass of noncommercial fruits and total mass of fruits; and physical-chemical characteristics of the fruits: pH, soluble solids, titratable acidity, ratio soluble solids/titratable acidity, reducing sugars, pectin, ascorbic acid, phenolic compounds and anthocyanins. The results were submitted to analysis of variance and the means to the Dunett test. Heritability was also estimated, genotypic and phenotypic variance and residual covariance, required for the Smith Index (1936) and Hazel (1943). With the simultaneous application of the three indices was observed a high frequency of hybrids obtained from crosses in which Camarosa was female genitor and Aromas male genitor. The crosses with the highest number of selected hybrids were Camarosa x Sweet Charlie both for in natura consumption as for industry. The attribution of distinct weights resulted in different selection and classification of hybrids.